(untitled) (Vietnam Journal of Community Medicine, 2026)
1) Objective: This study aimed to describe ocular manifestations and identify associated factors among patients with chronic kidney disease undergoing maintenance hemodialysis at Nam Dinh General Hospital. 2) Methods: A descriptive cross-sectional study was conducted in September 2025 among 36 patients with end-stage chronic kidney disease receiving maintenance hemodialysis, comprising 68 examined eyes. Fisher’s exact test and univariable linear regression were used to examine associations between age group, hemodialysis duration, and ocular abnormalities. 3) Results: The mean age was 58.46 ± 14.95 years, and males accounted for 63.9%. A hemodialysis duration of more than 60 months was observed in 61.0% of patients. Conjunctival–corneal calcification was present in 73.5% of eyes, most commonly grade 1 (45.6%). Mixed-type cataract accounted for 70.6%, and 19.1% had undergone intraocular lens implantation. Retinal vascular changes and hard exudates were observed in 89.7% and 67.6% of eyes, respectively. Significant differences were found between age group, hemodialysis-duration group, and cataract morphology (p < 0.001). 4) Conclusion: Hemodialysis duration was also associated with conjunctival–corneal calcification and retinal abnormalities. Ocular manifestations were highly prevalent in this population. Periodic ophthalmologic screening should be prioritized, particularly these patients receiving hemodialysis.